Cell cycle control by Xenopus p28Kix1, a developmentally regulated inhibitor of cyclin-dependent kinases. - Shou, W (1996)
We have isolated Xenopus p28Kix1, a member of the p21CIP1/p27KIP1/p57KIP2 family of cyclin-dependent kinase (Cdk) inhibitors. Members of this family negatively regulate cell cycle progression in mammalian cells by inhibiting the activities of Cdks. p28 shows significant sequence homology with p21, p27, and p57 in its N-terminal region, where the Cdk inhibition domain is known to reside. In contrast, the C-terminal domain of p28 is distinct from that of p21, p27, and p57. In co-immunoprecipitation experiments, p28 was found to be associated with Cdk2, cyclin E, and cyclin A, but not the Cdc2/cyclin B complex in Xenopus egg extracts. Xenopus p28 associates with the proliferating cell nuclear antigen, but with a substantially lower affinity than human p21. In kinase assays with recombinant Cdks, p28 inhibits pre-activated Cdk2/cyclin E and Cdk2/cyclin A, but not Cdc2/cyclin B. However, at high concentrations, p28 does prevent the activation of Cdc2/cyclin B by the Cdk-activating kinase. Consistent with the role of p28 as a Cdk inhibitor, recombinant p28 elicits an inhibition of both DNA replication and mitosis upon addition to egg extracts, indicating that it can regulate multiple cell cycle transitions. The level of p28 protein shows a dramatic developmental profile: it is low in Xenopus oocytes, eggs, and embryos up to stage 11, but increases approximately 100-fold between stages 12 and 13, and remains high thereafter. The induction of p28 expression temporally coincides with late gastrulation. Thus, although p28 may play only a limited role during the early embryonic cleavages, it may function later in development to establish a somatic type of cell cycle. Taken together, our results indicate that Xenopus p28 is a new member of the p21/p27/p57 class of Cdk inhibitors, and that it may play a role in developmental processes.